واقع ممارسات تنمية المديرين للتطوير التنظيمى بالمستشفيات الحكومية - الخطيب، محمود أحمد; مصطفى، أبو بكر محمد (جامعة حلوان - كلية التجارة وإدارة الاعمال, 2017)
استهدف هذا البحث دراسة ممارسات تنمية المديرين بالمستشفيات الحكومية المصرية، وذلك من خلال توصيف هذه الممارسات؛ بغرض التحقق من فروض البحث باستخدام أسلوب التحليل النوعي للبيانات، ولقد أسفر ذلك عن عدد من النتائج أهمها: -معظم الدورات التدريبية داخله وزارة الصحة التي يتبع لها المستشفيات محل الدراسة وجد أنها تركز في الأساس على الشق الفني الطبي وقلة وندوة الدورات التدريبية الخاصة بالتنمية الإدارية وإن وجدت فإنها عامة وغير متخصصة. -معظم المستشفيات محل الدراسة لا يوجد بها وحدات خاصة للتدريب داخل هذه المستشفيات وأن اعتماد هذه المستشفيات على دورات إدارية خارجها. -ممارسات التنمية الإدارية في المستشفيات محل الدراسة لا تدعم التطوير التنظيمي بهذه المستشفيات. -وجود بعض المعوقات التي تحول دون تطبيق أساليب تنمية المديرين الحديثة في المستشفيات الحكومية.
This research aims at investigating the practices of the development of managers in Egyptian government hospitals. This is carried out by describing and analyzing these practices using the qualitative analysis of factual data in order to test research hypotheses. The main findings of the research are: - Most of the training courses within the Ministry of Health followed by the hospitals under study were found o focus mainly on the technical aspects of health care and medical services, with the absence of management development programs. - Most of the hospitals under study do not have special units for training within these hospitals. Thus, these hospitals resort to outsourcing via external centers to train their managers. -It was found that Management development practices in the hospitals under study do not support the organizational development of these hospitals. - There are some obstacles that prevent the application of modern methods of managers development in public hospitals.
Keywords: المستشفيات الحكومية -- مديرو المستشفيات -- التنمية الإدارية -- مصر